Morphological and Some Wood Properties of Juniperus Oxycedrus Subsp. Macrocarpa in Derna Region, East Libya. (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
This work was designed to evaluate morphologic properties of leaf, cone and seed and to clarify the taxonomy of this species. The study also investigated some of the wood properties (specific gravity, fiber length) of Juniperus oxycedrus subsp. macrocarpa tree grown in Derna region in the east of Libya. The morphological properties (leaf length, leaf width, seed size and cone size) resulted have been observed to be important for taxonomy of this species. Also, the Pearson coefficient correlation among morphological parameters showed a positive correlation. On the other hand, results indicated that the specific gravity values ranged between (0.392-0.386). When study the relationship between specific gravity and cambial age. The general trend showed that the relationship was negative with age, where it was clear specific gravity values decreased with the increase in distance from the marrow of pith. The values of the R2 ranges from 59.9% -70.9%, and when examining the relationship between fibre length and cambial age, there was a positive effect; fibre length increased radically from pith to bark. Also, J. xycedrus subsp. macrocarpa tree is a short fibre wood with a mean fiber length of 1.75 mm.
Keywords: morphological properties; Juniperus oxycedrus subsp. macrocarpa wood; Libya